New genera and species of Paraboloponina (Hemiptera: Cicadellidae: Drabescini) from Indonesia - Lu, Lin; Zhang, Yalin (Zootaxa, 2023)
Guineapona monolophos gen. & sp. nov. and Canopyana apicospina sp. nov. are described from Indonesia. These two leafhopper genera are placed in the subtribe Paraboloponina, based on the elongate antenna, placement of antennal pits near the upper corners of the eyes and crown with transverse striations or carinae on the anterior margin.